Obstetric Surgical Site Infections: 2 Grams Compared With 3 Grams of Cefazolin in Morbidly Obese Women. Issue 4 (October 2015) - Ahmadzia, Homa K.; Patel, Emily M.; Joshi, Dipa; Liao, Caiyun; Witter, Frank; Heine, R. Phillips; Coleman, Jenell S.
Abstract : OBJECTIVE: To estimate whether morbidly obese gravid patients were less likely to develop a surgical site infection after receiving a higher dose of preoperative prophylactic antibiotics. METHODS: A retrospective cohort study of morbidly obese pregnant women undergoing cesarean delivery was conducted at two tertiary care centers from 2008 to 2013. Exposure was defined as receiving 2 g compared with 3 g cefazolin preoperatively. Disease was defined by diagnosis of a surgical site infection using Centers for Disease Control and Prevention criteria. We estimated a sample size of 141 patients in each group for a 67% reduction (15% to 5%) in risk for a surgical site infection. RESULTS: There were 335 women included in the cohort with a median absolute weight of 310 (interquartile range 299–333) pounds. Forty-four (13.1%) women were diagnosed with a surgical site infection. There was no difference in surgical site infection among those women who received 2 g compared with 3 g cefazolin (13.1% [23/175] compared with 13.1% [21/160]; P =.996). Labor (crude odds ratio [OR] 2.31, 95% confidence interval [CI] 1.21–4.40), internal labor monitoring (OR 2.78, 1.45–5.31), blood loss greater than 1, 500 mL (OR 2.15, 1.09–5.78), and staple closure (OR 2.2, 1.15–4.21) were associated with a surgical site infection among the entire cohort. After multivariable analysis, blood loss greater than 1, 500 mL (adjusted OR 3.32, 1.32–8.37) and staple closure (adjusted OR 2.45, 1.19–5.02) remained associated with an increased risk for a surgical site infection, whereas 3 g cefazolin still was not associated with reduced risk for a surgical site infection (adjusted OR 1.33, 0.64–2.74). CONCLUSION: In our multicenter retrospective cohort study, preoperative 3 g cefazolin prophylaxis administered to morbidly obese gravid patients did not reduce surgical site infections. LEVEL OF EVIDENCE: III Abstract : Administration of 3 g cefazolin preoperatively to morbidly obese gravid patients does not significantly reduce the risk for surgical site infection.